The effect of schema-based training on dispositional reasoning components : comparing frame-of-reference training and schema-feedback training - Hall, Jonathan (Organisational Psychology, 2015)
Prior research shows that accurate interviewers have higher ‘dispositional reasoning’, defined as the ability to understand the relationship between personality, behaviour and situations. Drawing on schema theory, the present study attempted to determine if dispositional reasoning could be developed in students who participated in interview training. We used two different experiments to assess the relative effectiveness of two different training approaches to enhance the subcomponents of dispositional reasoning: trait induction, trait extrapolation and trait contextualisation. Our first experiment used traditional frame-ofreference (FOR) training in an attempt to develop dispositional reasoning. In a second experiment, we developed schema-feedback training, a novel approach to training dispositional reasoning that is based on the use of schema refinement through feedback. We found that neither approach had an effect on the participants’ dispositional reasoning component scores when compared to a ‘no-training’ comparison group. The low statistical power (due to a relatively small sample size) was a limitation in this study. Further research is necessary to determine the malleability of interviewers’ dispositional reasoning.